PENYEMPURNAAN SIFAT PAPAN SERAT BERKERAPATAN TINGGI DARI CAMPURAN RUMPUT GELAGAH, TANDAN KOSONG KELAPA SAWIT, DAN BAMBU - Dian Anggraini Indrawan; Han Roliadi; Rossi Margareth Tampubolon; Gustan Pari; Adi Santoso; Mohamad Iqbal (Jurnal Penelitian Hasil Hutan, 2015)
Laboratory-scale manufactured hardboard made of Saccharum Sponaneoun Grasses (SSG), Empty Oil-palm Bunches (EOPB), and andong bamboo is potentially developed. However, initial experiment shows the hardboard did not meet Japanese Industrial Standard (JIS) and International Standard Organization (ISO) for hardboard. This paper observes modification of the hardboard to satisfy the standards. Modification includes adding alkali concentration during pulp cooking and changing the additives composition. Result shows modification can enhance the hardboard quality to satisfy JIS and ISO requirements. Fiber mixture of SSG pulp and andong/betung bamboo pulp was cooked in 10.5% alkali concentration; and 12% alkali concentration for EOPB pulp. Additives composition used were tannin-resorcinol formaldehyde/TRF adhesive, alum, and activated charcoal; without wax emulsion. The mixture of SSG pulp (50%) + EOPB pulp (50%) was the most prospective for hardboard, followed by SSG pulp (100%) solely; SSG pulp (50%) + andong bamboo pulp (50%); and SSG pulp (50%) + betung bamboo pulp (50%) as the lowest prospects. The least prospective fibrous material (betung bamboo) are expectedly be improved by using more TRF adhesive, nano-size activated charcoal and cross-linking agents.